Investigating cosmology models through usual and dual kaniadakis entropies: theoretical and observational tensions and features - H. R. M. Zarandi; Y. Toda; E. Ebrahimi (European Physical Journal C: Particles and Fields)
Abstract We investigate cosmological models inspired by usual and dual Kaniadakis entropy, constraining them using observational data from CMB, BAO, supernovae, and $$H_0$$ H 0 measurements. Our analysis shows that while the base Kaniadakis models fail to resolve cosmic tensions, their extensions, incorporating dynamic dark energy or non-flat geometry, exhibit improved consistency. Negative values for the Kaniadakis parameter $$β $$ β are observationally preferred, favoring the dual entropy formulation. The models are further analyzed for stability, cosmic age predictions, and large-scale structure formation, demonstrating their viability as alternatives to standard cosmology.